The unidentified skeletal collection of Capuchos cemetery (Santarém) housed at the University of Coimbra - José, Andreia (2022)
The aim of this article is to present to the scientific and academic community a new osteological collection housed at the Department of Life Sciences from the University of Coimbra (Portugal), the Unidentified Skeletal Collection of the Capuchos Cemetery. The skeletons were collected from the same cemetery as those of the 21st Century Identified Skeletal Collection, however their identity is unknown. The collection is comprised of 73 individuals, of which 68 are adults of both sexes (34 females, 33 males, and one individual of unknown sex) and five are non-adult individuals. It is estimated that the majority of adult individuals have a European ancestry.